Perceived role of primary care physicians in Nova Scotia's reformed health care system. Qualitative study. - Sangster, L. M. (College of Family Physicians of Canada, 1999)
OBJECTIVE: To determine primary care physicians' perceptions of their role in a reformed health system. DESIGN: Qualitative study using in-depth interviews. SETTING: Province of Nova Scotia. PARTICIPANTS: Purposefully selected sample of 14 practising primary care physicians. MAIN OUTCOME FINDINGS: Participants identified seven aspects of their role: primarily, diagnosis and treatment of patient's medical problems; then coordination, counseling, education, advocacy, disease prevention, and gatekeeping. The range of activities and degree of responsibility assumed by participants, however, varied. Factors affecting role perception fell into three categories: philosophical view of health and medicine, willingness to collaborate, and practical realities. Participants differed in their understanding of primary health care and their overall vision of the health system. Remuneration policies and concerns about sharing accountability were factors preventing an integrated, collaborative approach to care. Personal, patient, and structural realities also limited physicians' roles. CONCLUSIONS: This sample of primary care physicians had diverse perceptions of their role. Results of this study could provide information for identifying issues that need to be addressed to facilitate changes taking place in the health care system.